Long Distance Communication Between Children and Parents: (Study on Out-of-town Students of FISIP Unismuh Makassar) - Ayunda, Magfira; Pratiwi M, Indah (Jurnal Komunikasi dan Organisasi (J-KO), 2025)
This research explores the dynamics of long-distance communication between children and their parents, focusing on students from the Faculty of Social and Political Sciences at Muhammadiyah University of Makassar who live apart from their families. Effective communication within the family plays a vital role in shaping emotional well-being and personal stability for students living away from home. Utilizing a qualitative descriptive method, the study gathered data through interviews, observations, and documentation. Grounded in Koerner and Fitzpatrick's Family Communication Patterns theory, the research categorizes family interactions into four types: consensual, pluralistic, protective, and laissez-faire. The results show that students from consensual and pluralistic families tend to receive greater emotional support and sustain closer relationships with their parents. On the other hand, those from protective and laissez-faire family backgrounds often encounter limited interaction and emotional distance, leading to heightened psychological stress. Communication is further challenged by factors such as geographic separation, academic demands, and unstable internet access. This study enhances our understanding of how family communication functions in long-distance scenarios and highlights the need for universities to offer stronger emotional and social support for students living away from home.